GLOBALIZATION CHANGES AS NEW DEVELOPMENT IMPERATIVES WORLD ECONOMY: CHALLENGES FOR INTERNATIONAL MARKETING - Резнікова, Наталія В.; Іващенко, Оксана А.; Курцев, Олексій Ю. (Journal of Strategic Economic Research, 2023)
The purpose of the article is to conceptually rethink the strategic challenges to international marketing caused by the fragmentation of the world economy and the greening of the global international economic development agenda. The main vector of the company's development is determined by the global marketing strategy, which, in turn, includes the following varieties: internationalization strategy (implies the development and consolidation in new markets); diversification strategy (based on expanding the range of goods and services); segmentation strategy (increasing the number of customers by increasing coverage in different market segments); cooperation strategy (based on cooperation and partnership with other enterprises on terms beneficial to both parties); globalization strategy (consists of working on the basis of market qualities that do not depend on a particular country). Among the globalization changes affecting the imperative of revising the global marketing strategy, we included the following: (1) fragmentation of the world economy and disintegration processes; (2) protectionism in international economic policy; (3) trade wars; (4) price wars; (5) the transition from global competition to global rivalry; (6) gaps in global value chains and global supply chains; (7) implementation of friendshoring and reshoring models; (8) global inflation and the cost of living crisis in leading economies; (9) reduction in global demand; (10) development of the digital and digitized economy; (11) development of green and circular economy; (12) chaos of innovation processes; (13) development of electronic commerce; (14) formation of new markets; (15) formation of new business models; (16) formation of new payment systems; (17) asymmetric application of consumer demand activation mechanisms; (18) review of retail principles; (19) formation of new consumption patterns; (20) demographic changes; (21) formation of ethical consumerism; (22) fair trade request. Conceptualizing, developing, and implementing an effective global marketing strategy has been found to be a major challenge, because "global strategy" involves combining competitive advantages arising from geographic location, economies of scale, or global distribution of brands by ensuring a global presence, protecting domestic dominance, and overcoming fragmentation between countries. It is noted that the set of globalization changes affects the development of global development strategies, which can be supplemented by hyper-rivalry strategies and deglobalization strategies.